A Common Fixed Point Theorem in Fuzzy Metric Space Using the Property (CLRg): Manish Jain, Sanjay Kumar - Team, Support (Thai Journal of Mathematics, 2016)
In this paper, we generalize the results of Kumar and Fisher [S. Kumar, B. Fisher, A common fixed point theorem in fuzzy metric space using property (E.A.) and implicit relation, Thai J. Math. 8 (3) (2010) 439–446.] using weakly compatible mappings along with property (CLRg). We also provide an example in support our result.